Economic sentiment indicators and foreign direct investment: Empirical evidence from European Union countries - Andrzej Cieślik; Mahdi Ghodsi (The Vienna Institute for International Economic Studies (wiiw), 2021)
This paper studies the role of business sentiment in the decisions of multinational enterprises (MNEs) to undertake foreign direct investment (FDI) across European Union (EU) member states. Based on the knowledge-capital model, the study employs the Pseudo Poisson Maximum Likelihood (PPML) estimator and panel data to examine empirically the determinants of FDI across EU member states during the period 2003-2017. The empirical evidence suggests that better economic sentiment in an EU Member State induces MNEs to undertake FDI in that country, while worse economic sentiment in an EU member state motivates an MNE in that country to invest abroad.
Keywords: F21; F23; 330; economic sentiment; factor endowments; foreign direct investment; multinational enterprise; market size; EU Member States